2014
DOI: 10.14260/jemds/2014/2584
|View full text |Cite
|
Sign up to set email alerts
|

The Antitubercular Drug Induced Adverse Effects in Registered Cases Under RNTCP – Dots, Programme in Bijapur

Abstract: AIM:The aim of this study is intended to make an effort to determine the incidence of adverse effects and the risk factors for developing side effects against anti-TB drugs. DESIGN:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(5 reference statements)
1
0
0
Order By: Relevance
“…On the similar lines a study conducted by Athira B et al, 12 found out the maximum burden of ADRs has been carried by age group of 50-70 years with the mean age of 44.92 ± 17.22 years. Similarly the study conducted by S. Nemagouda et al, 13 found that the maximum incidence of ADRs occurred in the age group of 41-60 years with the mean age of patients developing ADR to be 45.26 ± 13.45 years.…”
Section: Fig 4: Incidence Pattern Of Adrs In Different Sites Of the supporting
confidence: 61%
“…On the similar lines a study conducted by Athira B et al, 12 found out the maximum burden of ADRs has been carried by age group of 50-70 years with the mean age of 44.92 ± 17.22 years. Similarly the study conducted by S. Nemagouda et al, 13 found that the maximum incidence of ADRs occurred in the age group of 41-60 years with the mean age of patients developing ADR to be 45.26 ± 13.45 years.…”
Section: Fig 4: Incidence Pattern Of Adrs In Different Sites Of the supporting
confidence: 61%